"They Were There for People Who Needed Them": Student Attitudes Toward the Use of Trigger Warnings in Victimology Classrooms. Issue 1 (2nd January 2019) - Cares, Alison C.; Franklin, Cortney A.; Fisher, Bonnie S.; Bostaph, Lisa Growette
Abstract : Over the last five years, vigorous debate has been waged about the purpose, use, and impact of trigger warnings in courses offered at institutions of higher education. This debate has been largely uninformed by research findings. This study fills this gap using quantitative and qualitative data collected via surveys in a large undergraduate victimology course to explore student attitudes toward trigger warnings. Findings revealed considerable, but nuanced support for trigger warning use in victimology courses. Support does not appear to differ between crime victims and non-victims; support is higher among females than males. These findings underscore that universal decisions mandating or advocating for or against the use of trigger warnings are premature. Further study is needed with a diverse range of samples to gain a fuller picture of student attitudes about trigger warnings as well as to assess any impact of trigger warnings use on student behavior and learning.